The strengthening of local structures, with special reference to amalgamation and co-operation between municipalities in Council of Europe member states . Reorganisation of local authorities and inter-authority co-operation in member states; Umschlagt. - (:unkn) unknown (My University, 1974)
Dargestellt und verglichen wird die Entwicklung der Kommunalreformen in den einzelnen europäischen Ländern. Kritisiert wird, daß nur in wenigen Staaten die Öffentlichkeit einen Einfluß auf den Planungsprozeß genommen habe.
Keywords: Kommunalreform; Regionalreform; Regionalplanung; Verwaltung; Planung